2021
DOI: 10.3390/jcm10225330
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Supports Decision Making during Open-Chest Surgery of Rare Congenital Heart Defects

Abstract: The human right ventricle is barely monitored during open-chest surgery due to the absence of intraoperative imaging techniques capable of elaborating its complex function. Accordingly, artificial intelligence could not be adopted for this specific task. We recently proposed a video-based approach for the real-time evaluation of the epicardial kinematics to support medical decisions. Here, we employed two supervised machine learning algorithms based on our technique to predict the patients’ outcomes before che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Artificial intelligence (AI), with its applications in the form of machine learning (ML) and deep learning (DL) among many, has emerged as a tool aiding the creation of personalized intervention plans as well as an accurate data extractor to ascertain potential post-operative sequelae [ 80 ]. The supervised machine learning models such as k-nearest neighbor classifier (KNN) and support vector machine classifier (SVM) have also aided in the intra-operative assessment of cardiac fluid kinematics, which are significant determinants of successful congenital heart surgeries [ 81 ]. The subsequent post-operative management of CHDs is imperative for maintaining the structural fluid dynamics and thus the prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Artificial intelligence (AI), with its applications in the form of machine learning (ML) and deep learning (DL) among many, has emerged as a tool aiding the creation of personalized intervention plans as well as an accurate data extractor to ascertain potential post-operative sequelae [ 80 ]. The supervised machine learning models such as k-nearest neighbor classifier (KNN) and support vector machine classifier (SVM) have also aided in the intra-operative assessment of cardiac fluid kinematics, which are significant determinants of successful congenital heart surgeries [ 81 ]. The subsequent post-operative management of CHDs is imperative for maintaining the structural fluid dynamics and thus the prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reported that AI applications can support clinician decision making (4,7,10,13,16,17,19,21,23,24,26,28,(30)(31)(32)(33)35,38). Machine learning models improve clinician's medical decisions by providing better preoperative risk assessment, stratification and prognostication (10,17,21,24,(30)(31)(32)35,38). AI applications could also guide clinicians on how aggressive prophylactic measures are given such as increased patient monitoring or giving additional therapies (4,13,33).…”
Section: B Clinician Outcomesmentioning
confidence: 99%
“…The relevance of the models described, mixed to an engineering approach, brought to a faster and more efficient elaboration of the information, with high potential and flexibility across different fields 54 58 .In fact, the use of machine learning (ML) in biology and medicine allowed to unveil correlations and phenomena hidden in the vast amount of data, outperforming the analysis of experts in the field, for example in the interpretation of the electrocardiogram 59 63 . Supervision is based on previously labeled reference datasets which are used to train ML algorithms to predict the class of each unlabeled data point 58 . Classification has already been used in the in-vitro context for several tasks, for instance, to check the quality of CM derived from differentiated human iPS cells 64 or to identify healthy or diseased CM from the contractile profile 64 .…”
Section: Introductionmentioning
confidence: 99%